Topographic Precipitation Diagnosis: Model Design and Validation in a Two-Dimensional Context - Xiangqian Wei; Yi Liu; Cong Cheng; Xinyu Chang; Jun Guo (Atmosphere)
This study develops a two-dimensional (z-x direction) atmospheric dynamics model based on a set of simplified atmospheric motion equations, designed for rapid simulation of atmospheric flow characteristics over complex terrains. The model effectively captures the influence of topography on the atmospheric flow field, offering a new research tool for the in-depth investigation of atmospheric dynamic phenomena under complex terrain conditions. Furthermore, the model takes into account water vapor transport and condensation processes, and employs a simplified algorithm for the conversion of cloud droplets to raindrops to estimate the intensity and spatial distribution of precipitation. The innovative use of the z-coordinate system allows for a focused simulation of dynamic processes in complex terrains, capable of real-time computation of the temporal variations in precipitation processes. The model exhibits high simulation precision and has a wide range of potential practical applications.